2015
DOI: 10.1007/s12289-015-1240-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and modelling air mass flow rate in the injection stretch blow moulding process

Abstract: The injection stretch blow moulding process involves the inflation and stretching of a hot preform into a mould to form bottles. A critical process variable and an essential input for process simulations is the rate of pressure increase within the preform during forming, which is regulated by an air flow restrictor valve. The paper describes a set of experiments for measuring the air flow rate within an industrial ISBM machine and the subsequent modelling of it with the FEA package AbaqusABAQUS. Two rigid cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…In previous research by the authors [10,25], the amount of air flow rate governing the rate on inflation of the preform was shown to be an important variable. In these experiments the air flow rate could be varied by adjustment of the line pressure and adjustment of a flow restrictor which had dimensionless settings 0 to 6 i.e.…”
Section: Air Flow Ratementioning
confidence: 94%
See 2 more Smart Citations
“…In previous research by the authors [10,25], the amount of air flow rate governing the rate on inflation of the preform was shown to be an important variable. In these experiments the air flow rate could be varied by adjustment of the line pressure and adjustment of a flow restrictor which had dimensionless settings 0 to 6 i.e.…”
Section: Air Flow Ratementioning
confidence: 94%
“…For the purposes of these trials the line pressure was fixed to 8 bar and the flow restrictor input was set to 2, 4 and 6, corresponding to an air mass flow rate of 9, 23 and 36 g/s respectively. In previous research the evolving cavity temperature was recorded and revealed a quasi-adiabatic 'polytropic' process [25] and it was shown that assuming isothermal conditions was appropriate for accurately capturing the air flow behaviour. Understanding this air flow is critical when forming a suitable FEA simulation.…”
Section: Air Flow Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the successful investigation of stretch blow moulding by free stretch blow for PET bottles [32][33][34][35][36], this article describes a technique for characterising the behaviour of PLLA tubes for stretch blow moulding of BVS. A novel experimental setup by processing tubes within a water bath has been introduced to ensure isothermal conditions, overcoming the surface cooling problems from exposure in the atmosphere during transfer from heating station to blow station.…”
Section: Introductionmentioning
confidence: 99%
“…It was hard to control the final thickness of the plastic bottle. Some blow molding methods such as the stretch-blow modling had been simulated using FEM [10][11][12][13]. They had used a preform which was controlled its thickness using the plastic injection method.…”
Section: Introductionmentioning
confidence: 99%